The Effect of Co-Branding, Brand Trust, and E-WOM on Interest in Buying Aerostreet Brand Shoes on Adolescents in Kudus Regency (Institut Agama Islam Negeri Kudus, 2023)
This study is to empirically examine the effect of co-branding, brand trust, and e-WOM on the interest in buying Aerostreet brand shoes in adolescents in Kudus Regency, using a quantitative approach and a type of causal associative research. The population of teenagers aged 17-24 years who know Aerostreet brand shoes (whether they have or have never made a purchase) and live in Kudus Regency, as many as 100 research samples. Data analysis techniques use multiple regression analysis methods with the help of SPSS data processing program version 20 for windows. The results showed that all variables had a significant effect on the interest in buying Aerostreet brand shoes in adolescents in Kudus Regency either partially or simultaneously, therefore the results of this study corroborated the research of Nella Bintari Anjarwati, Tri Cuong DAM, and Muslih Mughoffar.Keywords: Co-Branding, Brand Trust, E-WOM, and Buying Interest